2022
DOI: 10.7166/33-1-2521
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Effect of the Iso 9001 Quality Management System on Small and Medium Enterprises in Gauteng, South Africa

Abstract: The implementation of quality management systems (QMS) is central to the performance of small and medium enterprises (SMEs). At present, there is a lack of information about the level of adoption and implementation of QMS by SMEs in Gauteng Province, even though that province has the highest number of SMEs in South Africa (SA). This study therefore aims to investigate the effect of the ISO 9001 QMS on SMEs in Gauteng. Quantitative research was conducted, and an online survey was used to collect data. An infere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…As reported by the authors of the articles (Palacios Guillem, 2019;Santos et al, 2011), the mentioned ISO 9001, ISO 14001 and EMAS systems are the most frequently implemented in SMEs. According to the literature review, it was shown that research in the area of ISO 9001 in SMEs mainly concerned: motivation and benefits from implementation (Khan and Farooquie, 2016;Magodi et al, 2022;Vasilevska and Rivza, 2018;Zimon et al, 2018), main problems occurring during implementation and certification (Unterreiner and Gisbert Soler, 2019), as well as the impact of increasing customer satisfaction with product quality (Usman et al, 2019). In the case of the ISO 14001 system and the EMAS system in SMEs, the research concerned, for example: the impact of the system on the substantive results of the company (Johnstone, 2022), type and application of sustainability controls (Johnstone, 2021), factors, barriers and benefits of implementation (Salim et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As reported by the authors of the articles (Palacios Guillem, 2019;Santos et al, 2011), the mentioned ISO 9001, ISO 14001 and EMAS systems are the most frequently implemented in SMEs. According to the literature review, it was shown that research in the area of ISO 9001 in SMEs mainly concerned: motivation and benefits from implementation (Khan and Farooquie, 2016;Magodi et al, 2022;Vasilevska and Rivza, 2018;Zimon et al, 2018), main problems occurring during implementation and certification (Unterreiner and Gisbert Soler, 2019), as well as the impact of increasing customer satisfaction with product quality (Usman et al, 2019). In the case of the ISO 14001 system and the EMAS system in SMEs, the research concerned, for example: the impact of the system on the substantive results of the company (Johnstone, 2022), type and application of sustainability controls (Johnstone, 2021), factors, barriers and benefits of implementation (Salim et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The implementation of the ISO 9001 standard in small and medium-sized companies tends to improve product quality, and increase productivity and customer satisfaction (Magodi et al, 2022). Based on the proposal, engineers have the potential to contribute technically and play a strategic role in this context.…”
Section: These Proposals Can Be Used In Different Materials Engineeri...mentioning
confidence: 99%
“…Similar al estudio sobre el efecto del ISO 9001 en las empresas pequeñas y medianas en Sudáfrica (Magodi et al, 2022) se validó la hipótesis con significancia (p-valor < 0.05) estadística acerca de la relación entre la implementación del ISO 9001 y la sostenibilidad de las empresas pequeñas y grandes.…”
Section: Marco Teórico Y Estudios De Investigaciones Aplicadas De Las...unclassified